Farmers’ Perception of Climate Variability and Change and Its Implication for Implementation of Climate-Smart Agricultural Practices - Saguye, Tesfaye Samuel (American Journal of Human Ecology, 2017)
The main purpose of this study was to assess farmers’ perception on climate change and variability and its implication for adoption of climate -smart farming practices. A multi stage sampling procedure used to select the sample respondent households and the total sample size of the study was 138 households. Primary data were collected by using semi-structured interview, focus group discussion (FGDs) and key informant interviews. Both descriptive statistics and binary Logistic regression model were used as data analysis techniques for this study. The descriptive statistics analysis results indicated that about 88.73% of farmers believe that temperature in the district had become warmer and also over 90% respondents were recognized that rainfall volume, pattern, distribution and timing has changed, resulting in increased frequency of drought for prolonged period of time and high intensity rainfall for short periods of time. Though the majority of the responders perceived climate change problems, only 62.56 percent of the total respondents’ adopted climate-smart agricultural practices while the remaining 37.5 percent has not adapted climate change-smart agricultural practices. This could imply that though perception, knowledge and awareness of climate change and variability are at frontline prerequisite sequentially for adoption of climate change-smart agricultural practices decisions, it is not cure-all alone factor. The output of the binary logistic regression analyses proved that age of the household head, gender, education, farm experience, household size, and distance to the nearest market, access to irrigation water, local agro-ecology and access to information on climate change through extension services were found to have significant influence on the probability of farmers to perceive climate change and variability. With the level of perception to climate change being more than that of adaptation, the study suggests that more policy efforts should be geared towards helping farmers to adapt to climate change.